Teisme, Mesianisme Dan Aksiologisme: Akomodasi Kitab Suci Kristen Terhadap Problema Kemiskinan Dan Pemiskinan - Deky Nofa Aliyanto (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2021)
AbstractPoverty and impoverishment are social realities that have been struggling for most of the world community to this day. Christians who are part of society that form social fibers with the stereotype of